Sustainable mining in the Northernmost Europe : lessons learned and practices developed - Lesser, Pamela; Ejdemo, Thomas; Suopajärvi, Leena; Petrétei, Anna (Luleå tekniska universitet, Samhällsvetenskap, 2016)
The SusMinNor project is a collaboration between the Regional Council of Lapland, the University of Lapland, and Luleå University of Technology. The project’s duration spans 2015-2016 and is funded with financial support from Interreg Nord. There have been two project workshops, one in Haparanda, Sweden in April 2016 for researchers engaged in the subject, and the closing seminar, during which the research results were disseminated, in Rovaniemi, Finland in September 2016. The Synthesis Report is the main deliverable of the project and highlights the major research themes in the social science literature on sustainable mining in Finland and Sweden (not Norway unfortunately as the project partner dropped out), and in addition, also identifies good practices and knowledge gaps in the current research. SusMinNor